The Role of GSK3β in T Lymphocytes in the Tumor Microenvironment - Dimou, Anastasios; Syrigos, Konstantinos N. (Frontiers in Oncology, 2020)
Immunotherapy options for patients with cancer have emerged following decades of research on immune responses against tumors. Most treatments in this category harness T cells with specificity for tumor associated antigens, neoantigens and cancer-testis antigens. GSK3β is a serine-threonine kinase with the highest number of substrates and multifaceted roles in cell function including immune cells. Importantly, inhibitors of GSK3β are available for clinical and research use. Here, we review the possible role of GSK3β in the immune tumor microenvironment, with goal to guide future research that tests GSK3β inhibition as an immunotherapy adjunct.